The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12978-021-01165-0
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure to social network members among abortion-seeking women in low- and middle-income countries with restrictive access: a systematic review

Abstract: Background Health care for stigmatized reproductive practices in low- and middle-income countries (LMICs) often remains illegal; when legal, it is often inadequate, difficult to find and / or stigmatizing, which results in women deferring care or turning to informal information sources and providers. Women seeking an induced abortion in LMICs often face obstacles of this kind, leading to unsafe abortions. A growing number of studies have shown that abortion seekers confide in social network mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Fear of social stigma and rejection shaped participants’ pathways for information-gathering, echoing findings from other contexts [ 15 17 ]. These concerns reflect a reality for many women, who are often ostracized, isolated, and sometimes forced to leave their communities if they are found to have had an abortion [ 23 25 ].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Fear of social stigma and rejection shaped participants’ pathways for information-gathering, echoing findings from other contexts [ 15 17 ]. These concerns reflect a reality for many women, who are often ostracized, isolated, and sometimes forced to leave their communities if they are found to have had an abortion [ 23 25 ].…”
Section: Discussionmentioning
confidence: 67%
“…Incomplete and inaccurate information often leads to misperceptions about risks, efficacy, and safety, deterring women from seeking care within formal healthcare settings [ 14 ]. Despite inadequate knowledge, research has found that women often limit their discussion of their abortion decisions to few, select people or keep the decision to abort entirely a secret, out of fear of stigmatization and potential rejection from family, friends, and partners [ 15 17 ]. Fear of stigmatization may be greater in a highly Catholic country like the DRC given the church’s prominent role in society and its opposition to abortion.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles about abortion/TOP in midwifery are not enough to arrive at a universally applicable theory, but it is a solid beginning. In low- and middle-income countries, access to abortion care is sometimes restricted or hidden and information lacking [ 36 ]. Often, illegal drug sellers, people working with illegal providers, sex workers, taxi drivers, or feminist groups are key informants in the search for abortion providers.…”
Section: Discussionmentioning
confidence: 99%
“…It will be important to use new approaches to reach women that are not reaching facility-level care. WHO is currently exploring network-based methods 20 to better understand how women’s social networks can deter or refer her to reach safe abortion care services.…”
Section: Women’s Experiences Of Postabortion Carementioning
confidence: 99%